Translation and initial validation of the Medication Adherence Report Scale (MARS) in Italian patients with Crohn's Disease. Issue 5 (May 2019) - ,; Scribano, Maria Lia; Caprioli, Flavio; Michielan, Andrea; Contaldo, Antonella; Privitera, Antonino Carlo; Bozzi, Rosa Maria; Calabrese, Emma; Castiglione, Fabiana; Ciccaglione, Antonio Francesco; Delle Fave, Gianfranco; Bodini, Giorgia; et al.
Abstract: The MARS-5 (Medication Adherence Report Scale) was developed in English. The aim of this project was to analyse the MARS-5I (© Prof Rob Horne) psychometric properties and to identify whether its Italian translation is suitable for assessing medication adherence in Crohn Disease (CD) Italian patients. The MARS was translated and linguistically validated in Italian. The MARS-5I was used for evaluating medication adherence in the SOLE study, conducted in Italy on 552 subjects with CD. In order to un-bias the questionnaire results from the effects of treatment change and/or effectiveness, the analyses were performed on the 277 patients whose disease activity remained stable, selected among the 371 patients who maintained the same treatment between two consecutive visits. Internal consistency was high (Cronbach's alpha of 0.86). Pearson's correlation coefficient was 0.50 (p < 0.001) and 0.86 (p < 0.001- outliers removed), indicating satisfactory test-retest. MARS 5I scores were not correlated with Treatment Satisfaction Questionnaire for Medication but a small and statistically significant correlation was shown with physician-evaluated medication adherence, indicating convergent validity. MARS-5I, the Italian translation of the English MARS, showed satisfactory internal consistency and test-retest, and a low but statistically significant convergent validity. We confirmed the utility of this tool in patients with CD.